Strengthening Knowledge Management Practices in Kathmandu’s Community Colleges - Gautam, Tara Prasad (Journal of Productive Discourse, 2025)
Knowledge management (KM) has emerged as a crucial factor in enhancing institutional efficiency, innovation, and competitive advantage in higher education. However, its adoption in community colleges remains underexplored, particularly in developing regions such as Nepal. This study investigates the awareness, perceptions, and implementation of KM practices in community colleges within the Kathmandu Valley, with a focus on knowledge acquisition, organization, and application. Adopting a pragmatic philosophical paradigm, the study employs a convergent parallel mixed-methods approach, integrating quantitative surveys (n=300) and qualitative in-depth interviews (n=50) to ensure a comprehensive understanding of KM practices. A cross-sectional descriptive research design allows for the simultaneous collection of numerical data and contextual insights. Stratified random sampling ensures representativeness in the quantitative phase, while purposive sampling is used to identify key informants for the qualitative analysis. This study contributes to the existing body of KM research by providing empirical evidence on KM adoption in community colleges, highlighting the need for strategic interventions, faculty training, and ICT-driven solutions to enhance knowledge processes. The findings offer practical recommendations for policymakers and academic institutions to develop a structured KM framework, fostering a knowledge-driven culture in Nepalese higher education.